The Leadership Role of the International Class Program (ICP) Coordinator in Building a Productive Academic Culture - Muwafiqus Shobri (Harmony Philosophy: International Journal of Islamic Religious Studies and Sharia, 2024)
This study aims to analyze the leadership role of the International Class Program (ICP) coordinator in fostering a productive academic culture at Madrasah Aliyah (MA) Hasan Jufri Lebak Sangkapura Gresik. Specifically, this study explores the leadership role of ICP coordinators, the challenges they face, and the impact of this leadership on student academic achievement. This study uses a qualitative approach with a case study design, and data is collected through in-depth interviews, participatory observations, and document studies. Key informants include principals, vice principals, ICP coordinators, teachers, and students. Data analysis uses thematic methods to identify the main patterns and themes. The study’s findings show that ICP coordinators actively facilitate teacher collaboration, create a supportive learning environment, and conduct regular evaluations to improve teaching methods. The coordinator also organizes an additional mentoring program that enhances students’ understanding of the international curriculum, resulting in a 3.6% increase in students' final exam scores over the past two years. The main challenges in implementing ICP include limited technological resources and the need for teacher training in delivering the international curriculum. This study concludes that the transformational leadership of ICP coordinators is crucial in shaping an academic culture that supports student achievement. This research provides practical insights for educational institutions in optimizing the role of special program coordinators to build a productive academic culture.